MYSTERY OF NATICID PREDATION HISTORY SOLVED: EVIDENCE FROM A 'LIVING FOSSIL' SPECIES - Kase T.; Ishikawa M. (My University, 2003)
Observations of living Cernina fluctuata (Sowerby), the sole extant species of the Mesozoic and Cenozoic prosobranch gastropod family Ampullospiridae, show that this species is an algal grazer and is not a shell-drilling, predatory naticid gastropod. All Jurassic and Early Cretaceous gastropods previously assigned to Naticidae belong to Ampullo spiridae and are now inferred to be herbivores, not shell-drillers. This finding refutes the Triassic origin and favors a Cretaceous origin for naticid drilling predation. A preliminary revision of Cenozoic and Cretaceous species previously assigned to Naticidae suggests that naticids were absent prior to the Cretaceous Campanian and diversified at a modern level in Eocene time. This pattern of naticid diversification from the Late Cretaceous onward coincides roughly with the evidence of naticid predation. The fossil record of naticid drill holes once of anomalously short duration now accurately reflects the geologic history of naticid predation activity.
Keywords: PREDATION; HISTORY; FOSSILS; GEOLOGY; Jurassic; Triassic; Eocene; Campanian; Mesozoic::Jurassic; Кайнозой::Палеоген::Эоцен; Мезозой::Триасовая; Мезозой::Юрская; Mesozoic::Triassic; Мезозой::Меловая::Верхний::Кампанский; Cenozoic::Paleogene::Eocene; Mesozoic::Cretaceous::Upper::Campanian